Pengaruh Jus Buah Kiwi Hijau (Actinidia Deliciosa) Terhadap Perubahan Warna Pada Proses Pemutihan Gigi Secara In Vitro (Laporan Penelitian) - Delfiana Simatupang; Ade Prijanti Dwisaptarini (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
Background: Dental bleaching is a teeth enlighten process that also omit the teeth enamel and the dentin colour. Chromogen from food and drink that is people consumed might causing an external dischloration. One of material that could decrease the external dischloration and enlight the teeth colour is oxalic acid. Oxalic acid are abundant in green kiwi fruit (Actinidia deliciosa). Purpose: To examine the effect of green kiwi juice (Actinidia deliciosa) toward colour changing in dental bleaching. Methods: The used samples are 20 premolar teeth which passed a measurement colour process that is done both before and after the probation. The measurement is done by Spectrophotometer Vita easyshade. The samples were divided into 2 groups, they are the group which is soaked for an hour in 100% green kiwi juice (Actinidia deliciosa) and the controlled group which is covered by 35% carbamide peroxide for an hour. The experiment is done for 14 days. Result: The experiment shows the existence of colour changing after the immersion process in 100% green kiwi juice (Actinidia deliciosa) with significant result or significantly different of (colour’s changing total) is about (p≤0,05) before and after the test. Here, the samples are brighter after the immersion inside green kiwi juice (Actinidia deliciosa) with increasing value (lightness). Conclusion: Green kiwi fruit (Actinidia deliciosa) is a potentially material for dental bleaching as the effect of external dischloration.